Good Governance dalam Perspektif Hukum Islam Kontemporer (Tinjauan Usul Fikih dari Teori Pertingkatan Norma) - Ahmad Zayyadi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2018)
The concept of good governance on Usu>l al-Fiqh perspective is directed towards how to utilize the methods offered in the science of Usu>l al-Fiqh to formulate Islamic legal principles to respond to the latest problems of all issues, and here I will specifically address the issue of good governance in the perspective of contemporary Islamic law. In this case, seeing the many problems, especially the corruption of governance, requires us to examine the current reality of these governance conditions for better, professional, responsible, trustworthy, and so on. One of them is by developing the concept of good governance with the hope of contributing to the development of better bureaucratic governance in accordance with the principles and values ​​in Islamic law such as equality, tolerance (tasa>muh), justice, welfare, consultation (syu>ra>), honesty, objectivity (comprehensiveness) and so on become an indication of good and clean governance. The approach used is the Usu>l al-Fiqh approach as the epistemological and philosophical basis in Islamic law by describing the theory of new Usu>l al-Fiqh as applied theory in exploring the values ​​of public services (good bureaucracy–good governance or other terms that can be called clean governance) in the eyes of contemporary Islamic law.